1998
DOI: 10.1055/s-1998-2005
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Photoreactions in Two-Component Crystals

Abstract: This paper overviews the photochemical reactions of two-component crystals and solid mixtures. It covers mixed crystals, hydrogenbonded cocrystals, donor-acceptor crystals, inclusion crystals, crystalline organic salts (including Lewis acid complexes), and solid mixtures. Solid-state sensitization and quenching and solid-state asymmetric syntheses are also mentioned. Emphasis is placed on the synthetic points. Neither details of reaction mechanisms nor crystal structures are described in most cases. Yoshikatsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 104 publications
(157 reference statements)
0
26
0
Order By: Relevance
“…Then ca. 10 mg of each sample was placed in a special quartz vessel [25,26] and was irradiated for 0.5 h under the stream of Ar gas at 0°C. After the irradiation, the sample was dissolved in MeCN, followed by the addition of benzophenone as the standard to determine the amounts of 2 and 3, and then the solution was analyzed with HPLC.…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Then ca. 10 mg of each sample was placed in a special quartz vessel [25,26] and was irradiated for 0.5 h under the stream of Ar gas at 0°C. After the irradiation, the sample was dissolved in MeCN, followed by the addition of benzophenone as the standard to determine the amounts of 2 and 3, and then the solution was analyzed with HPLC.…”
Section: Synthesismentioning
confidence: 99%
“…The decomposition of the diperoxides 1 stopped at low conversions and the HPLC retention times of 1 differed very much from those of 2 and 3 (retention times with 90/10 MeOH-H 2 O: trans-1 9.4, cis-1 8.2, 2 2.6, 3 3.0 min; retention times with 65/35 MeOH-H 2 O: trans-1 [ 60, cis-1 [ 60, 2 10.8, 3 18.9 min). Furthermore, irradiation of all parts of the solid sample equally was difficult with our set-up [25,26], although the powder was mixed with a spatula from time to time. Therefore, determinations of the diperoxide recovery were subjected to large experimental errors as seen from Fig.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…For example, by forming host-guest complexes, cyclodextrins mediate photoreaction of aromatic guests such as anthracene, 5 coumarin 6 and stilbene 7,8 derivatives in solution as well as in the solid state. 8,9 However, few studies reported large rate acceleration and high stereo-and/or regioselectivity in [2 + 2] photoreactions mediated by cyclodextrins in solution.…”
mentioning
confidence: 99%